1998
DOI: 10.1098/rspb.1998.0296
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic evidence for parallel evolution in a marine gastropod, Littorina subrotundata

Abstract: Littorina subrotundata from wave-exposed rocky shores differ consistently in shell and radula morphology from those found in wave-protected salt-marshes. To determine if the two morphological forms of this gastropod represent separate species, clades, or ecotypes, DNA sequencing and single-stranded conformational polymorphism (SSCP) analysis were used to assay variation in a 480 bp fragment of the mitochondrial cytochrome-b gene. Several nested analyses of molecular variance (AMOVA) were then performed to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 24 publications
3
20
0
Order By: Relevance
“…The morphology of shells might be more often subject to parallel evolution than we have thought so far. Evidence for parallel evolution of two morphological forms has been found before in the marine gastropod Littorina subrotundata by Kyle and Boulding (1998). These authors conclude that the different forms are ecotypes.…”
Section: Evolution Of the Clausilial Apparatussupporting
confidence: 54%
“…The morphology of shells might be more often subject to parallel evolution than we have thought so far. Evidence for parallel evolution of two morphological forms has been found before in the marine gastropod Littorina subrotundata by Kyle and Boulding (1998). These authors conclude that the different forms are ecotypes.…”
Section: Evolution Of the Clausilial Apparatussupporting
confidence: 54%
“…The finding of largely species-specific radula types and the correlation between trophic morphology and substrate in Tylomelania as well as marked niche differences in species von Rintelen et al, 2007) suggest a strong role for ecological factors in speciation in these snails. In gastropods, studies on intertidal marine species of Littorina have indicated differentiation across ecotones and assortative mating between morphs (Johannesson et al, 1995;Kyle & Boulding, 1998;Wilding et al, 2001). The limnic gastropods of Sulawesi offer excellent opportunities to test the importance of these factors in freshwater.…”
Section: Speciation Patternsmentioning
confidence: 99%
“…Species of gastropods have been even more extensively investigated. The genus Littorina, for example, has a long history of study [see recent works by Reid et al (1996), Grahame et al (1997), Tatarenkov & Johannesson (1998), and Kyle & Boulding (1998)]. Other genera that have been recently analyzed include Hydrobia (Ponder & Clark, 1988), Stramonita (Liu et al, 1991), Alviniconcha (Denis et al, 1993), Trochus (Borsa & Benzie, 1993), Tectus (Borsa & Benzie, 1993), Austrocochlea (Parsons & Ward, 1994), Drupella (Johnson & Cumming, 1995), Columbella (Oliverio, 1995), Patella (Côrte-Real et al, 1996a,b;Ridgway et al, 1998), Nassarius (Sanjuan et al, 1997), Nucella (Kirby et al, 1997;Marko, 1998), and Dendronotus (Thollesson, 1998).…”
Section: Molluscamentioning
confidence: 99%
“…The multipronged attack on the population structure of Crassostrea across the Gulf of Mexico and Atlantic coast of North America (see most recently Hare & Avise, 1998) has shown that different techniques can give fundamentally different answers for reasons that still remain unclear. In Littorina, closely related pairs of taxa that occur in different habitats have in some studies been shown to exhibit reproductive barriers across environmental gradients within a site but, in other cases, samples from different environments within sites are more similar genetically than are those samples which are geographically isolated but environmentally similar (Kyle & Boulding, 1998;Tatarenkov & Johannesson, 1998). Some of this complexity is probably due to the proximity of the divergences being studied in all three genera (see Discussion), but is such complexity lying below the surface in the many other groups that have yet to be investigated so intensively?…”
Section: Molluscamentioning
confidence: 99%